1999
DOI: 10.1084/jem.189.4.627
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Dendritic Cells with Skin Endothelium: A New Perspective on Immunosurveillance

Abstract: The goal of this study was to determine the mechanisms by which dendritic cells (DCs) in blood could interact with endothelium, a prerequisite to extravasation into tissues. Our results indicate that DCs express both HECA-452–reactive and nonreactive isoforms of P-selectin glycoprotein ligand 1 (PSGL-1) and can tether and roll efficiently on E- and P-selectin under flow conditions in vitro. Freshly isolated blood DCs were further observed to roll continuously along noninflamed murine dermal endothelium in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
155
1
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(165 citation statements)
references
References 41 publications
8
155
1
1
Order By: Relevance
“…Although increased numbers of DCs have been reported in different tissue models of inflammation (41,58,69), the relative importance of recruitment from blood vs resident tissue sources has not been well established. For this reason, the source of DCs in the blister fluids is an important question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although increased numbers of DCs have been reported in different tissue models of inflammation (41,58,69), the relative importance of recruitment from blood vs resident tissue sources has not been well established. For this reason, the source of DCs in the blister fluids is an important question.…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, we found that two synthetic lipoprotein analogues were highly effective at recruiting cellular elements, DCs and memory/effector T lymphocytes, required for primary and/or secondary immune responses. Trafficking of DCs, as well as T cells, into skin is mediated by CLA and other isoforms of P-selectin glycoprotein ligand 1, which are expressed constitutively in PB (37,58). Therefore, it is highly likely that the enrichment for CLA ϩ T cells and DCs in the blister fluids reflected the expression of receptors for these molecules (i.e., E-and P-selectin) by activated vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Skin DCs capture antigen and up-regulate a number of surface antigens and traffic to DLNs, where they prime naïve T cells to become effector cells that can home to the skin (19,20). TSLP expression in AD is associated with Langerhans cell migration and activation in situ, and TSLP has been shown to promote the ability of DCs to polarize naïve T cells into Th2 cells partly by up-regulating OX40L on these cells (7,8,21).…”
Section: Skin Dcs Migrate Normally To Lymph Nodes Of Tslpr ؊/؊ Mice Andmentioning
confidence: 99%
“…CD44, CD62P ligand, and cutaneous lymphocyte-associated antigen) and chemokine receptors (e.g. CXC chemokine receptor-1, -2, and -3 and CC chemokine receptor-1 through -7) (6,(13)(14)(15)(16). Finally, DC elaborate a wide variety of cytokines (interleukin (IL)-1␤, IL-6, IL-12, and tumor necrosis factor-␣) and chemokines (IL-8, macrophage inflammatory protein-1␣ and -1␥, DC-chemokine-1, and thymus-expressed chemokine) (17)(18)(19)(20)(21), thereby regulating the magnitude and direction of T cell activation.…”
mentioning
confidence: 99%